Tribal assignment of the genus Eumera Staudinger, 1892, using multi-gene analysis, with description of a new species from Iran (Lepidoptera: Geometridae: Ennominae) - Wanke, Dominic; Shirvani, Asghar; Hausmann, Axel; Murillo-Ramos, Leidys; Sihvonen, Pasi (Zootaxa, 2023)
The geometrid moth genus Eumera Staudinger, 1892 consists of five yellow-orange-pinkish species distributed in the western Palearctic, with uncertain tribal classification within the geometrid subfamily Ennominae. In this study, we explored the phylogenetic position of the genus Eumera. Therefore, a concatenated dataset was analyzed, which includes one mitochondrial and up to ten protein-coding genetic markers per taxa. Moreover, we compared some external and internal morphological traits to other closely related genera. Our phylogenetic inference and comparative morphology suggested that Eumera should be included in the tribe Prosopolophini. In addition, a new species, Eumera rajaeii sp. nov. Wanke & Shirvani is described from southern Iran, and diagnosed by molecular data and morphological features. The distribution of the Iranian species is shown on a map. We illustrate external characters and male genitalia of three closely related Eumera species.